Exploring the Efficacy of Fractional Carbon Dioxide Laser as an Add-on Combination to Conventional Therapies for Treatment-Resistant Vitiligo (A Review Article): Enhancing vitiligo treatment with fractional CO2 laser: a promising approach - Mansouri, Parvin; Rahbar, Mohammadreza; Nilforouszadeh, Mohammad Ali; Shati, Mohsen (Journal of Lasers in Medical Sciences, 2023)
Introduction: Vitiligo, a dermatological disorder that leads to depigmented skin patches, presents a significant challenge, particularly in resistant areas such as acral regions. Fractional CO2 laser therapy holds promise as an adjunct to conventional treatment, enhancing repigmentation. This review comprehensively explores its efficacy and safety in resistant-to-treatment vitiligo. Methods: We conducted extensive database searches in PubMed, Embase, and Cochrane, focusing on English-language literature published between 2012 and 2023. We included comparative studies that met the following criteria: (1) Participants had non-segmental vitiligo, with resistant-to-treatment localization engagement; (2) The treatment involved the use of fractional CO2 laser in combination with conventional therapies; and (3) Outcomes were assessed based on the repigmentation ratio or significant difference. We excluded studies from which data from published results could not be extracted. Results: After extensive screening of 52 articles, we finally selected five studies. The results showed that fractional CO2 laser therapy, when combined with other treatments, often shows promise in vitiligo treatment in refractory cases. Although individual responses varied, overall efficacy and safety were promising, with minimal adverse effects and no severe complications. Conclusion: The fractional CO2 laser, when used in conjunction with conventional therapies, emerges as a promising option for treating refractory vitiligo. Large-scale randomized trials and a deeper understanding of the underlying mechanisms are vital for future progress in optimizing treatment protocols, case selection, and safety.